Pengaruh Pelatihan Aku Dan Targetku Terhadap Motivasi Belajar Matematika Pada Siswa SMP “X” - Sandayanti, Vira; Nugraha, Sumedi; Rachmahana, Ratna Syi'fa (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aimed to determine the effect of the training called “Me and My Target” on the motivation of learning Mathematics in 36 second grade students of